Acetic Acid Treatment Enhances Drought Avoidance in Cassava (Manihot esculenta Crantz) - Utsumi, Yoshinori; Utsumi, Chikako; Tanaka, Maho; Ha, Chien Van; Takahashi, Satoshi; Matsui, Akihiro; Matsunaga, Tomoko M.; Matsunaga, Sachihiro; Kanno, Yuri; Seo, Mitsunori; Okamoto, Yoshie; Moriya, Erika; et al. (Frontiers in Plant Science, 2019)
The external application of acetic acid has recently been reported to enhance survival of drought in plants such as Arabidopsis, rapeseed, maize, rice, and wheat, but the effects of acetic acid application on increased drought tolerance in woody plants such as a tropical crop “cassava” remain elusive. A molecular understanding of acetic acid-induced drought avoidance in cassava will contribute to the development of technology that can be used to enhance drought tolerance, without resorting to transgenic technology or advancements in cassava cultivation. In the present study, morphological, physiological, and molecular responses to drought were analyzed in cassava after treatment with acetic acid. Results indicated that the acetic acid-treated cassava plants had a higher level of drought avoidance than water-treated, control plants. Specifically, higher leaf relative water content, and chlorophyll and carotenoid levels were observed as soils dried out during the drought treatment. Leaf temperatures in acetic acid-treated cassava plants were higher relative to leaves on plants pretreated with water and an increase of ABA content was observed in leaves of acetic acid-treated plants, suggesting that stomatal conductance and the transpiration rate in leaves of acetic acid-treated plants decreased to maintain relative water contents and to avoid drought. Transcriptome analysis revealed that acetic acid treatment increased the expression of ABA signaling-related genes, such as OPEN STOMATA 1 (OST1) and protein phosphatase 2C; as well as the drought response and tolerance-related genes, such as the outer membrane tryptophan-rich sensory protein (TSPO), and the heat shock proteins. Collectively, the external application of acetic acid enhances drought avoidance in cassava through the upregulation of ABA signaling pathway genes and several stress responses- and tolerance-related genes. These data support the idea that adjustments of the acetic acid application to plants is useful to enhance drought tolerance, to minimize the growth inhibition in the agricultural field.